Dynamic changes in the abundance and chemical speciation of dissolved and particulate phosphorus across the river‐lake interface in southwest Lake Michigan. (4th February 2016) - Lin, Peng; Guo, Laodong
Abstract: Phosphorus (P) concentrations and primary production in the Great Lakes have declined since the 1980s, but changes in biogeochemical cycling pathways of different P species remain poorly understood. Water samples were collected for the measurements of different P species to examine the dynamics of P in the water column across the river‐lake interface from the Milwaukee River to open Lake Michigan. Dissolved inorganic P (DIP) concentrations were as high as 3049 nM in river waters, but decreased dramatically to as low as 11 ± 7 nM in open lake waters. Total dissolved P was mostly measured in the form of DIP in river waters (73% ± 18%), whereas dissolved organic P (DOP) became the predominant species (85% ± 18%) in lake waters. Colloidal P (>1 kDa) comprised 58% ± 16% of the bulk DOP in river waters, but decreased to 23% ± 5% in ologotrophic lake waters, showing again contrasting biogeochemical regimes between river and lake waters. Biological processes and coagulation/sedimentation were largely responsible for the removal of river‐derived P species and active transformation between inorganic and organic P occurred in both dissolved and particulate phases across the river‐lake interface. Increased water column P inventory over the winter of 2013–2014 likely resulted from an accumulative effect of both atmospheric and riverine inputs in the upper water column, and benthic nepheloid layer processes coupled with quagga mussels excretion for the lower water column, respectively. High partition coefficient values (log K d of 4.33–7.01) and a "particle concentration effect" on the partitioning of P between dissolved and particulate phases attested the particle‐reactive nature of P in lake waters.